2013
DOI: 10.1037/a0031328
|View full text |Cite
|
Sign up to set email alerts
|

Differences in response initiation and behavioral flexibility between adolescent and adult rats.

Abstract: Adolescence is a period of increased vulnerability to psychiatric illnesses such as addiction, mood disorders, and schizophrenia. Rats provide a useful animal model for investigating the differences in behavior and biology between adults and adolescents that stem from ongoing brain development. We developed the Cued Response Inhibition Task, or CRIT, to assess response inhibition and initiation processes by measuring the ability of rodents to withhold a response during an inhibitory cue and then to respond pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
38
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 60 publications
11
38
2
Order By: Relevance
“…Thus, despite similar testing ages for the adult groups in ours and the previous studies (Simon et al, 2013, Newman & McGaughy, 2011, the age and presumed pubertal status of the adolescent groups may contribute to inconsistent findings. Future studies are required to pinpoint the precise role that these various methodological factors play in laboratory rodent assessments of age and sex differences in behavioral flexibility.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Thus, despite similar testing ages for the adult groups in ours and the previous studies (Simon et al, 2013, Newman & McGaughy, 2011, the age and presumed pubertal status of the adolescent groups may contribute to inconsistent findings. Future studies are required to pinpoint the precise role that these various methodological factors play in laboratory rodent assessments of age and sex differences in behavioral flexibility.…”
Section: Discussioncontrasting
confidence: 47%
“…Rodent studies of age differences in behavioral flexibility that use positive (food) or negative (escape from water) reinforcement have reported mixed results (Simon, Gregory, Wood, & Moghaddam, 2013;Newman & McGaughy, 2011;Willing, Drzewiecki, Cuenod, Cortes, & Juraska, 2016), with factors such as pubertal onset potentially contributing to disparate findings . Studies of age differences in reward processing also highlight the importance of the peripubertal period in males, as there is a peripubertal peak in motivation for (Friemel, Spanagel, & Schneider, 2010) and consumption of palatable reward (Friemel et al, 2010;Marshall, Liu, Murphy, Maidment, & Ostlund, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Simon, Gregory, Wood, and Moghaddam (2013) describe a cued response inhibition task, which is similar to the stop-signal task described above. This task begins with illuminated nose poke holes in which the animals may respond for a reward, and an inhibitory tone.…”
Section: Impulsive Behavior: Definition and Measurementmentioning
confidence: 99%
“…In animal research, adolescent rats have shown deficits in cognitive flexibility, but not necessarily impulsivity in stop tasks (Simon, Gregory, & Moghaddam, 2013). Premature responses in the 5-Choice Serial Reaction Time Task were greater in adolescent rats than adults (Burton & Fletcher, 2012).…”
Section: Review Of Impulsive Behavior and Drug Use In Adolescence mentioning
confidence: 99%
See 1 more Smart Citation